Local Bi ordering in MOVPE grown Ga(As, Bi) investigated by high resolution scanning transmission electron microscopy. (March 2017) - Beyer, Andreas; Knaub, Nikolai; Rosenow, Phil; Jandieri, Kakhaber; Ludewig, Peter; Bannow, Lars; Koch, Stephan W.; Tonner, Ralf; Volz, Kerstin
Graphical abstract: Highlights: Atomic resolution STEM images of Ga(As1− x Bi x ) are investigated with respect to Bi clustering. Preferential ordering along 〈100〉 and 〈101〉 is found. Electronic structure calculations show the energetic favorability of these configurations. Abstract: The distribution of Bi atoms in Ga(As, Bi) samples on an atomic scale is investigated using aberration corrected high angle annular dark field imaging. With the help of statistical evaluations, it is shown that the Bi atoms are not randomly distributed. Instead, Bi ordering along the 〈100〉 and 〈101〉 crystallographic directions with chain lengths of up to 5 atoms is identified. Performing electronic structure calculations shows that this chain-like Bi arrangement is energetically favorable relative to isolated Bi atoms due to the stabilization by stronger bonds to shared Ga atoms and to in-plane Ga atoms.